2021
DOI: 10.1155/2021/9920421
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent Prediction and Optimization Algorithm for Chronic Disease Rehabilitation in Sports Using Big Data

Abstract: This paper investigates chronic diseases in the older population in the Chinese province of Henan and analyzes the rehabilitation needs and the current supply of related services in different levels of medical and elderly care institutions. We explore the fundamental causes for the diversified needs and insufficient supply of chronic disease patients in professional medical services and daily care. Using big data and deep learning (DL) in the sports domain, we propose a novel and intelligent prediction system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Apache Hadoop [18], [45] refers prominent Big Data platform with a significant supportive association. Existing technologies found complexity and low performance while analyzing and computing Big Data.…”
Section: ) Abilities Of Apache Hadoopmentioning
confidence: 99%
“…Apache Hadoop [18], [45] refers prominent Big Data platform with a significant supportive association. Existing technologies found complexity and low performance while analyzing and computing Big Data.…”
Section: ) Abilities Of Apache Hadoopmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%